The Effectiveness of Otis Urethrotomy Combined with Six Weeks Urethral Dilations Until 40 Fr in the Treatment of Bladder Outlet Obstruction in Women: A Prospective Study - Grivas, Nikolaos; Tsimaris, Ioannis; Makatsori, Aikaterini; Hastazeris, Konstantinos; Kafarakis, Vasillios; Stavropoulos, Nikolaos E (Urology Journal, 2014)
Abstract Purpose: To evaluate the effectiveness of Otis urethrotomy combined with six weekly urethral dilations until 40 French (Fr) in the treatment of women with urodynamic diagnosis of bladder outlet obstruction (BOO). Materials and Methods: Women diagnosed with lower urinary tract symptoms underwent urodynamic evaluation. Severity of symptoms and quality of life were assessed with international prostate symptom score (IPSS) and quality of life (QoL) questionnaires. Bladder outlet obstruction was defined as the presence of two or more of the following: maximum flow rate (Qmax) < 12 mL/s, detrusor pressure at maximum flow (PdetQmax) > 50 cmH2O and urethral resistance factor (URF) greater than 0.2. Ten out of 25 women diagnosed with BOO met the criteria. All women underwent Otis urethrotomy to 40 F and six-week urethral dilations until 40 F. After six months all patients underwent free uroflowmetry. Moreover post voiding residual (PVR), IPSS-QoL were recorded. Results: Six months post-operatively there was a significant improvement in all parameters: IPSS = 13.5 vs. 22.5 (P = .001), QoL = 3 vs. 5 (P = .001), voided volume = 312 mL vs. 216 mL (P = .055), Qmax = 27.5 mL/s vs. 12 mL/s (P = .001), and PVR = 27.5 mL vs. 170 mL (P = .005). Five women had close follow up during an average of 82 months. They maintained improved QoL (P < .005) and low PVR (P < .002). All other parameters lost their statistical significance. Conclusion: The described therapeutical modality seems to improve all clinical and urodynamic parameters in women with evidence of BOO not related to detrusor sphincter dyssynergia or obvious functional and anatomical pathology.